Prebiotics Must Achieve a Threshold of Increase in Gut Probiotic Bacteria to Impart Beneficial Health Effects on the Host. (29th May 2020) - Abernathy, Breann; Schoenfuss, Tonya; Bailey, Allison; Gallaher, Daniel
Abstract: Objectives: Prebiotic dietary fibers are dietary fibers that] are highly fermented in the large intestine, produce beneficial changes in the gut microbiome, and impart a health benefit to the host. Using reactive extrusion, we have synthesized a novel dietary fiber that is an oligosaccharide of polymerized lactose, which we term polylactose. Here we report on two studies feeding polylactose to rats to determine its prebiotic potential. Methods: In Exp. 1, the polylactose preparation contained 51% dietary fiber, 20% free lactose, 5% glucose, and 24% other materials. Rats were fed high fat diets containing 9% total dietary fiber, including cellulose (control, CE, 9%), polylactose (PL, 6%), polydextrose (PD, 6%), and fructooligosaccharide (FOS, 6%). In Exp. 2, the polylactose preparation contained 75% dietary fiber, 9% lactose, 3% glucose, and 13% other materials. Rats were again fed high fat diets containing 9% total dietary fiber, including CE (9%), polylactose (6% or 3%), PD (6%), and galactooligosaccharide (GOS, 6%). In both experiments, rats were fed for 10 weeks, then cecums (empty), cecal contents, livers, and epididymal fat pads were collected. In addition, body composition was determined by MRI. Results: In both experiments, final body weight and daily energy intake did not differ among the groups. In Exp. 1, feeding PL greatly increased cecum weight (an indicator of fermentation), cecal Bifidobacterium and Lactobacillus species abundance, increased cecal acetate and propionate, and reduced liver lipids and fat pad weight, compared to the CE group. While PD and FOS increased probiotic species and short chain fatty acids slightly (compared to CE), this was not to the same extent as PL and did not reduce fatty liver and adiposity. In Exp. 2, 6% PL increased cecum weight relative to 3% PF, PD and GOS, all of which were greater than CE. The cecal microbiome was similar among PL (both 3 and 6%), PD, and GOS, all of which differed from CE and were similar to PD and FOS from Exp. 1. Liver lipids, fat pad weight, and body composition did not differ among any of the groups. Conclusions: The prebiotic activity of polylactose differed depending on the preparation, for unknown reasons. However, our results suggest there is a threshold of probiotic bacteria abundance that must be attained before beneficial effects are imparted on the host by prebiotics. Funding Sources: Midwest Dairy Association.